Design and application of system with dual-control of water and electricity based on wireless sensor network and video recognition technology. (September 2018) - Chen, Hejie; Wu, Chunxue; Huang, Wending; Wu, Yan; Xiong, Naixue
In the industrial Internet of Things, water and electricity is the most important hidden project. Its requirements are very high, especially the intelligent control of water and electricity. Therefore, a design and application of system with dual-control of water and electricity is proposed and convolutional neural networks–based video recognition technology is used to identify the security issues that occur in the field. Some sensors are used to control the use of water and electricity, while others are used to collect scalar data which include user's data and video multimedia data in the wireless sensor network. The scalar data are used to update the user's database, and the video multimedia data are used to monitor and prevent anomalies from occurring in the field of dual-control of water and electricity. In order to solve the security problem of the user in wireless sensor network, this article proposes a radio frequency identification mutual security authentication protocol based on shared secret hash function. Finally, experiments show that the proposed secure authentication protocol can guarantee the secure transmission of data between the sensor node and the server, and the video recognition technology can recognize some abnormalities well.